Recuperação imunológica e alterações metabólicas em pessoas vivendo com HIV após o início da terapia antirretroviral: resultados de estudos seccionais e coortes históricas. - Cássia Cristina Pinto Mendicino (2020)
OBJECTIVES: To evaluate the health in people living with HIV (PLHIV) after long-term use of antiretroviral therapy (ART), assessing the immune recovery (IR) and occurrence of comorbidities. METHODS: The Study 1 was carried out to describe the changes in the HIV treatment guidelines (cross-sectional analysis of the period 2004-2018) and the IR in PLHIV, initiating ART in Minas Gerais state (historical cohort design; 2009-2018). The data were obtained from national databases. The median time to the achievement of IR (first T-CD4+ >500 cells/μl after ART) was calculated through the Kaplan-Meier curves and associated risk factors were assessed by the extended Cox proportional hazard regression models. In the Study 2 (historical cohort) the occurrence of comorbidities (hyperglycemia, hypertriglyceridemia, reduced HDL cholesterol and increased LDL cholesterol) was evaluated among PLHIV initiating ART in Belo Horizonte (2001-2005). Data were obtained through interviews, medical charts, physical evaluation, laboratory exams and dual-energy xray absorptiometry. The median time to outcome was estimated through the Kaplan-Meier curves and the associated risk factors were assessed by extended Cox proportional hazard regression models for multiple events. Additionaty, it was evaluated the total of comorbidities/individual (hyperglycemia, hypertriglyceridemia, reduced HDL cholesterol, increased LDL cholesterol, systemic arterial hypertension, low bone mineral density) after long-term use of ART through a cross- sectional study. The associated risk factors were assessed through quasi-Poisson regression. RESULTS: Study 1 - Among 60,618 PLHIV (67% male; 48% aged 25-39 years-old) the time to ART initiation decreased from 604 to 28 days. Only 36% of participants had T-CD4+ results recorded before ART initiation: median=302 cells/μl. Half of the participants had available viral load (VL) results after ART initiation, which reduced from 2.3 to 1.7 log10 copies/ml. The occurrence of IR was estimated in 8,014 participants: male: 67%, mean age=38.7 years-old, median baseline T-CD4+ count=228 cells/μl, median-baseline VL=4.7 log10 copies/ml. The IR incidence was 58%, corresponding to an incidence rate of 29.47 cases/100 person-years. The median-time to IR was 23 months. The T-CD4+ baseline count >350 cells/μl (hazard ratio (HR)=7.36; CI95%=6.79-7.98 and ART adherence (HR=3.09; CI95%=2.84-3.36) were risk factors for IR. Study 2 – In total, 188 PLHIV participated in the historical cohort (55% male <35 years-old, 51% median-baseline T-CD4+ count=185 cells/μl, median-baseline VL=4,0 log10cópias/ml). The incidence of metabolic alterations was 79% (incidence rate=11cases/100 person-years) and the median-time to outcome was 116 months. Age was associated with metabolic alterations (HR=1.03; CI95%=1.01-1.04). A total of 98 PLHIV was included in the cross-sectional study: 53% male, 55% > 52 years-old. 207 comorbidities were found (mean=2.1/participant): dyslipidemia: 71%, of systemic arterial hypertension: 52%, low bone mineral density: 45%, hyperglycemia 43%s. Age (OR=1.03; CI95%=1.02-1.04) and moderate physical activity (OR=1.84; CI95%: 1.08-3.13) were associated with comorbidities. DISCUSSION: The modest increase in T-CD4+ counts at ART initiation suggests late ART initiation in a considerable proportion of participants, who consequently did not achieve IR. In addition, the study showed a high frequency of comorbidities. However, it was not found significant associations between RI and a reduced risk of comorbidities or a delay in its ocurrence.